1997
DOI: 10.1007/s002880050475
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of the hard thermal loop expansion for quasi-real photons production

Abstract: We discuss the bremsstrahlung production of soft real and virtual photons in a quark-gluon plasma at thermal equilibrium beyond the Hard Thermal Loop (HTL) resummation. The physics is controlled by the ratio Q 2 /q 2 0 of the virtuality to the energy. When Q 2 /q 2 0 ≪ g 2 , where g is the strong coupling constant, the emission rate is enhanced by a factor 1/g 2 over the HTL results due to light-cone singularities and the bremsstrahlung is induced by scattering of the quark via both transverse and longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(131 citation statements)
references
References 33 publications
6
124
1
Order By: Relevance
“…for which n γ (ω) = 0. In this case, the photon population 7 When ρ(t i ) = exp(−H/T ), there is an explicit dependence of the initial density matrix on the coupling constant e. It is known that this dependence is taken care of without changing any formula, simply by appending a vertical branch to the time path [33], going from t i to t i −i/T . Moreover, it has been shown that the contribution of this vertical branch can be taken into account if one enforces the KMS condition at each intermediate step of the calculation [33,34,35].…”
Section: Photon-free Initial Statementioning
confidence: 99%
See 1 more Smart Citation
“…for which n γ (ω) = 0. In this case, the photon population 7 When ρ(t i ) = exp(−H/T ), there is an explicit dependence of the initial density matrix on the coupling constant e. It is known that this dependence is taken care of without changing any formula, simply by appending a vertical branch to the time path [33], going from t i to t i −i/T . Moreover, it has been shown that the contribution of this vertical branch can be taken into account if one enforces the KMS condition at each intermediate step of the calculation [33,34,35].…”
Section: Photon-free Initial Statementioning
confidence: 99%
“…These rates have been evaluated at 1-loop 1 in [3,4,5], at 2-loop in [6,7,8,9], and the Landau-Pomeranchuk-Migdal [10,11,12] corrections have been resummed in [13,14,15,16,17,18,19]. Up-to-date reviews of the situation regarding photon and dilepton production in equilibrium can be found in [20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The quarks interaction that occurs within the many quarks mater phases includes three important interaction (Compton scattering, annihilation and bremsstrahlung), these interactions occur at one time, But make a mental analysis in the study of these interactions, So that each separated by a phenomenon, when examined from the rest of the phenomena, Because of different a Mont of energy each interaction phenomenon for the rest of the phenomena, So one can understand the behavior of particles, According to the form of graphic curves in the search, we will prevail in this thesis to study the phenomenon of (bremsstrahlung) (Aurenche et al, 1997;Landau et al, 1953) in reaction (Quarkgluon).…”
Section: Resultsmentioning
confidence: 99%
“…It worth mentioning that the underlying physical processes in the one loop diagram are the 2 ↔ 2 processes, Compton and annihilation. However, it was shown [ 4,5,6] that bremsstrahlung and the new process of annihilation of an off-shell quark (on the left of figure 1) contribute to leading order. These processes appear only at the two loop level in the effective theory.…”
Section: A Surveymentioning
confidence: 99%